Increasing Nurse Professionalism During The COVID-19 Pandemic in Hospital Province Central Sulawesi - Sipatu, Lindanur; Natsir, H. Syahir; Adda, Harnida Wahyuni (International Journal of Social Sciences and Management, 2022)
Hospitals need comprehensive strategies and efforts in handling covid-19, one of the strategies is the management of Human Resources (HR) 2000. This study aims to analyze efforts to increase the professionalism of nurses during the covid-19 pandemic. This type of qualitative research with a case study approach. The study was conducted for 3 months in a hospital in Central Sulawesi Province. The number of informants consisted of: 11 implementing nurses, 3 team leaders and 3 committee heads (1 informant as team leader, also as chairman of the 2000 committee), 1 Covid team coordinator, 1 Head of Section 2000, 2 Heads of 2000 and 1 Director of the hospital and 1 secretary of PPNI Central Sulawesi Province. The analytical method refers to the theory of Miles, Huberman and Saldana (2014), namely the Interactive Analysis Model, using the Nvivo 12 Plus application technique for windows. The results of the research have 3 main themes: theme 1: Recruitment of covid nurses, theme 2: clinical authority of nurses, theme 3: delegation of authority. B The conclusion of this research is the discovery of 3 main themes, namely covid nurses, clinical nurse authority and authorized delegation. The recruitment of nurses through a credentialing process, clinical obligations and authorized delegation procedures is an effort to improve the professionalism of nurses. It is hoped that hospital management can improve the professionalism of nurses by optimizing the committee's duties, especially in the sub-field of credentials, providing support and recognition and equal attention to committees and medical committees. Int. J. Soc. Sc. Manage. Vol. 9, Issue-3: 120-131.